„Denn mit dem Pogrom war ich und werde gewesen sein“: Lotte Paepcke und die Missachtung von Juden in Deutschland nach der Shoah - Venzl, Tilman (Internationales Archiv für Sozialgeschichte der deutschen Literatur, 2012)
Axel Honneth’s theory of recognition is juxtaposed to Lotte Paepcke’s descriptions of the disrespect for Jews in Germany from the Weimar Republic, through the Third Reich, to the Federal Republic. While Paepcke’s depiction of the transitional time to National Socialism can be well understood in terms of Honneth’s theory as a continuous erosion of the various spheres of recognition, the theory is not fully adequate to describe her position on the German politics of memory of the postwar period. Paepcke is convinced that a renewed recognition of Jews in Germany after the Shoah can only be obtained by a broad acceptance of the concept of ‘negative symbiosis’ (Dan Diner), both publicly and individually.
Gesehen am 21.03.2018